2014
DOI: 10.1002/mc.22218
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐96‐5p influences cellular growth and is associated with poor survival in colorectal cancer patients

Abstract: Expression of miR-96-5p is frequently altered in various types of cancer and the KRAS oncogene has been identified as one of its potential targets. However, the biological role of miR-96-5p expression in colorectal cancer (CRC) and its ability to predict the clinical course of patients have not been investigated yet. In this study, we explored miR-96-5p expression in 80 CRC patients and evaluated the impact on clinical outcome by Kaplan-Meier curves and multivariate Cox proportional models. In vitro miR-96-5p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 30 publications
6
51
0
1
Order By: Relevance
“…We also validated the up‐regulation of miR‐96‐5p in the present study, which has been observed in many types of cancers, including triple‐negative breast cancer . It was found that up‐regulated miR‐96‐5p is associated with poor survival in patients with colorectal cancer and that it resulted in reduced cell proliferation . These findings indicate the role of miR‐96‐5p in tumor growth.…”
Section: Discussionsupporting
confidence: 86%
“…We also validated the up‐regulation of miR‐96‐5p in the present study, which has been observed in many types of cancers, including triple‐negative breast cancer . It was found that up‐regulated miR‐96‐5p is associated with poor survival in patients with colorectal cancer and that it resulted in reduced cell proliferation . These findings indicate the role of miR‐96‐5p in tumor growth.…”
Section: Discussionsupporting
confidence: 86%
“…Another miR that was highly dysregulated in TNBC samples was miR-96. Previous studies have shown miR-96 as a potential biomarker for bladder, colorectal, non-small cell lung cancer and acute myeloid leukemia 35-40. On the other hand, many of the miRs were found to be significantly downregulated in TNBC samples compared to adjacent normal tissues.…”
Section: Resultsmentioning
confidence: 91%
“…Among them, the role and biological significance of miR-96 have focused mainly on the oncogenesis and cancer progression in various malignancies, such as the liver, stomach, and breast cancer [2931]. Therefore, miR-96 is recognized as an oncomiR that facilitates the development of malignancies by promoting the growth, proliferation, and survival of cancer cells [32, 33]. On the other hand, the metabolic influence of miR-96 was first reported in pancreatic β-cells [34].…”
Section: Discussionmentioning
confidence: 99%